Factors Related To Hypertension Control Behavior In Hypertension Patients - Retno Mardhiati; Bunga Meilinda Nuryono; Dian Kholika Hamal (Jurnal Kesehatan Prima, 2023)
The increasing prevalence of hypertension every year is a public health problem today, so it is necessary to be active in controlling hypertension to reduce the risk of complications. Therefore, this study aims to determine the factors associated with hypertension control behavior in hypertensive patients in Tegal Parang Village, South Jakarta in 2022. This research is a quantitative research using a cross sectional study design. The population of this study was 1,180 hypertensive patients. The sample in this study was 178 respondents using the Cluster Sampling technique. The analysis used in this research is univariate and bivariate analysis using Chi Square test. The study found that from 178 hypertensive patients, 121 (68%) hypertensive patients did not do routine control, while 57 (32%) hypertensive patients did routine control. Based on statistical tests, it was concluded that there was a relationship between age (P-value 0.000), gender (P-value 1.000), education (P-value 0.041), time of suffering from hypertension (P-value 0.005), knowledge (P-value 0.033), attitude (P-value 0.435), access to health services. (P-value 0.601), family support (P-value 0.000) and support from health workers (P-value 0.000) with hypertension control behavior.That there is a significant relationship between age, education, time of suffering from hypertension, knowledge, family support and support from health workers with hypertension control behavior.